The experience of inhabiting the domestic interior as a way to rethink the apartment building - Otárola-Mora, Mauricio (2020)
As result of the increase in population in urban centers, a new type of building has had a greater impact on the urban landscape, the apartment tower. This typology changes the dynamics of socialization between neighbors and eliminates the neighborhood condition as they are separate architectural objects from the city. Due to economic interests, these developments have reduced living spaces as much as possible, offering units between 30 and 70 m2 without access to proper lighting and natural ventilation or outdoor spaces such as balconies or patios. The quality of life of the inhabitants is highly deteriorated due to these high-density housing formats, affecting moods and interpersonal relationships. This article analyzes the development of this typology, giving a historical and social perspective of its beginnings as part of modern architecture and its future potential in the current context. The objective of the study is to offer both architectural and social management and organization alternatives that allow real estate development that contributes to better sociability in the city and a better quality of life for its inhabitants. Emphasizing the symbiotic relationship between the small scale of the housing building and the domestic interior and the city as a collective construction.